Outcomes after metal-on-metal hip resurfacing: could we achieve better function? - Newman, M; Barker, K; Pandit, H; Murray, D (2008)
OBJECTIVE: To report functional outcomes after metal-on-metal (MOM) hip resurfacing. DESIGN: A cohort of 126 MOM hip resurfacing operations were reviewed 1 year after surgery. SETTING: Hospital trust specializing in orthopedic surgery. PARTICIPANTS: Sixty-seven right and 59 left hips were reviewed in patients (N=120; 71 men, 49 women; mean age, 56+/-9y; range, 24-76y). INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Administered once at follow-up. Function was measured using the Oxford Hip Score (OHS), Hip disability and Osteoarthritis Outcome Score, and UCLA Activity Score. Complications, pain, range of motion, Trendelenburg test, strength, walking, single-leg stand, stair climbing, and 10-m walk time were assessed. RESULTS: Overall examination was satisfactory with few complications. High functional levels were reported. The median OHS was 15 and median UCLA Activity Score 7 (active). For 25%, outcome was poor with persistent pain, reduced hip flexion (mean, 94.46 degrees +/-12.7 degrees ), decreased strength (P<.001), restricted walking, and functional limitations. CONCLUSIONS: Information about outcomes is important for patients undergoing surgery. Hip resurfacing remains an emergent technology, with further follow-up and investigation warranted. One explanation for suboptimal recovery may be current rehabilitation, originally developed after total hip arthroplasty. Rehabilitation tailored to hip resurfacing, paced for this active population and progressed to higher demand activities, may improve outcomes.